Detailed seismic attenuation structure beneath Hokkaido, northeastern Japan: Arc‐arc collision process, arc magmatism, and seismotectonics. Issue 8 (22nd August 2014) - Kita, Saeko; Nakajima, Junichi; Hasegawa, Akira; Okada, Tomomi; Katsumata, Kei; Asano, Youichi; Kimura, Takeshi
Abstract In this study, we imaged a detailed seismic attenuation structure (frequency‐independent Q−1) beneath Hokkaido, Japan, by merging waveform data from a dense permanent seismic network with those from a very dense temporary network. Corner frequency of each event used for t* estimation was determined by the S coda wave spectral ratio method. The seismic attenuation (Qp−1) structure is clearly imaged at depths down to about 120 km. For the fore‐arc side of Hokkaido, high‐Qp zones are imaged at depths of 10 to 80 km in the crust and mantle wedge above the Pacific slab. Low‐Qp zones are clearly imaged in the mantle wedge beneath the back‐arc areas of eastern and southern Hokkaido. These low‐Qp zones, extending from deeper regions, extend to the Moho beneath volcanoes, the locations of which are consistent with those of seismic low‐velocity regions. These results suggest that the mantle wedge upwelling flow occurs beneath Hokkaido, except in the area where there is a gap in the volcano chain. In contrast, an inhomogeneous seismic attenuation structure is clearly imaged beneath the Hokkaido corner. A broad low‐Qp zone is located at depths of 0–60 km to the west of the Hidaka main thrust. The location almost corresponds to that of the seismic low‐velocity zone in the collision zone. The fault planes of the 1970 M6.7 and 1982 M7.1 earthquakes are located at the edges of this broad low‐Qp zone. Observations in this study indicate that our findings contribute to understanding the detailed arc‐arc collision process, magmatism, and seismotectonics beneath Hokkaido.